Health data sharing in Germany: individual preconditions, trust and motives - Elias Kühnel; Felix Wilke (Frontiers in Public Health)
ObjectiveThe use of health data plays an important role in medical research. In Germany, the secondary use of health data is not yet as established as in other countries. In order to exploit the full potential of using health data, a key prerequisite is that a large part of the population is willing to share their health data. The aim of this study is to identify attitudes and factors that influence citizens’ willingness to share personal health data for medical research purposes.MethodsA standardized cross-sectional telephone survey was conducted among the German population aged 18 and above. The representative survey of a total of 1,004 people took place from December 7th to 21th, 2023. Multiple linear regression analyses were conducted to identify potential factors influencing the willingness to share health data.ResultsAround 43% of respondents are willing to share their health data with public research institutions, while around 17% are still undecided. The population, however, is particularly skeptical about data being shared with commercial companies. Less than a quarter of respondents (23%) would share their data with small and medium-sized enterprises and only 15 percent with technology companies. Regarding the factors influencing the willingness to share data with research institutions, three overarching factors can be named: (1) individual characteristics, in particular the level of education and technical competence, (2) individual motives, such as altruism as well as worries and concerns regarding health data sharing, and (3) trust in institutions, especially trust in science and technology companies.Discussion and conclusionAlthough the study shows a general openness towards sharing health data and underlines the importance of altruistic motives, social inequalities and concerns about health data sharing are also evident. Trust plays a particularly important role here, as it acts as a mediator between individual preconditions and individual motives. In order to exploit the full potential of secondary data use in medical research, comprehensive information of the public about data sharing and use as well as transparent and open communication are required to strengthen trust in the actors involved and the data sharing process.